2015
DOI: 10.1136/jech-2015-206040
|View full text |Cite
|
Sign up to set email alerts
|

Measurable effects of local alcohol licensing policies on population health in England

Abstract: BackgroundEnglish alcohol policy is implemented at local government level, leading to variations in how it is put into practice. We evaluated whether differences in the presence or absence of cumulative impact zones and the ‘intensity’ of licensing enforcement—both aimed at regulating the availability of alcohol and modifying the drinking environment—were associated with harm as measured by alcohol-related hospital admissions.MethodsPremises licensing data were obtained at lower tier local authority (LTLA) lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 19 publications
(18 reference statements)
1
61
1
Order By: Relevance
“…However, the price of cigarettes has increased linearly over time, so its impact would have been removed by differencing the time–series (that is, using the difference between successive values of the outcome variables rather than the values themselves) 34. Several alcohol policies came into effect during the study period, including the removal of financial incentives aimed at encouraging general practitioners to screen their patients for heavy drinking, a ban on the sale of alcohol below the total cost of duty and value‐added tax (VAT) combined in May 2014, and strengthening of local alcohol licensing policies 55, 56, 57, 58. Tobacco policies include the Children and Families Act which, in 2015, made it an offence for an adult to buy tobacco for anyone aged under 18 years (including proxy purchasing) and the revised Tobacco Products Directive in 2016 which mandated the introduction of plain packaging, a ban on packs containing fewer than 20 cigarettes and stricter e‐cigarette regulation 59, 60.…”
Section: Discussionmentioning
confidence: 99%
“…However, the price of cigarettes has increased linearly over time, so its impact would have been removed by differencing the time–series (that is, using the difference between successive values of the outcome variables rather than the values themselves) 34. Several alcohol policies came into effect during the study period, including the removal of financial incentives aimed at encouraging general practitioners to screen their patients for heavy drinking, a ban on the sale of alcohol below the total cost of duty and value‐added tax (VAT) combined in May 2014, and strengthening of local alcohol licensing policies 55, 56, 57, 58. Tobacco policies include the Children and Families Act which, in 2015, made it an offence for an adult to buy tobacco for anyone aged under 18 years (including proxy purchasing) and the revised Tobacco Products Directive in 2016 which mandated the introduction of plain packaging, a ban on packs containing fewer than 20 cigarettes and stricter e‐cigarette regulation 59, 60.…”
Section: Discussionmentioning
confidence: 99%
“…This provides a mechanism for local variation in the type of interventions delivered and the 'intensity' of delivery. De Vocht et al (2015) have found that 'intensity' of local licensing policies, which they defined as willingness to administer cumulative impact policies (explained below) and refuse licence applications, was associated with area-level reductions in alcohol-related 6 hospital admissions. This raises the possibility that variations in local licensing policy can influence area based inequalities in alcohol related harms.…”
Section: Introductionmentioning
confidence: 99%
“…Local variation has also been linked to variations in quality of service potentially leading to geographically unequal health outcomes (de Vocht et al, 2015). Reliance on local solutions for the national problem of alcohol related harms risks leading to unequal investment, delivery and effectiveness of local strategies.…”
mentioning
confidence: 99%
“…Recent encouraging findings on the likely beneficial impact of more pro-active regulatory policy approaches on the part of LAs on alcohol harm statistics such as hospital admission rates [25] and on the more traditional indices of crime and disorder [26], help strengthen the evidence case for public health teams in particular to make good use of their recently acquired 'responsible authority' status. Experience of the more pioneering LAs in this area also highlights that the way policies such as cumulative impact zones [27] and reducing the availability of cheap high alcohol content beverages [28] are implemented are likely to exhibit considerable variability according to local circumstances.…”
Section: Discussionmentioning
confidence: 99%